Estimation of serum lipids in patients with Oral Submucous Fibrosis in India - Ajai, Kratika (Medicina Oral S.L., 2014)
Objectives: Oral submucous fibrosis (OSMF) is the most prevalent precancerous condition in India. Low levels of lipids serves as a marker and prognostic indicator in the early detection of oral precancerous and cancerous states. In spite of the high prevalence and its potential to undergo malignant transformation, this condition has not widely been investigated with respect to the serum lipid levels. In the present study, an attempt was made to analyze the complete serum lipid profile, total cholesterol (TC), triglycerides (TG), high density lipoprotein (HDL) cholesterol, low density lipoprotein (LDL) cholesterol and very low density lipoprotein (VLDL) cholesterol in OSMF and controls. Material and Methods: The study was conducted in 45 clinically and histopathologically diagnosed cases of OSMF and 45 age and sex matched controls. The complete lipid profile including TC, TG, HDL cholesterol, LDL cholesterol and VLDL cholesterol was analyzed. Results: The serum lipid levels were significantly lower in the patients with OSMF than in the controls. When the values were compared between different disease stages, the maximum reduction of lipids was evident for stage 3 OSMF. From the present results, it is evident that the level of serum lipids decreases with progression of the disease. Conclusions: From these findings, it appears that the decrease in the lipid levels may be considered as a useful marker in the early diagnosis of oral premalignant condition like OSMF. Key words:Oral submucous fibrosis, lipids, premalignant condition.